PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN ANGGOTA PADA KOPERASI SIMPAN PINJAM (KSP) MITRA USAHA MANDIRI SUMATERA UTARA - Sagala, Roslinda; Silalahi, Esli (UNIKA Santo Thomas, 2022)
The purpose of this study is to analyze the effect of service quality on member satisfaction. With this aim, it is expected to identify the problem of how the quality of service of physical evidence (tangible), reliability (reliability), responsiveness (responsiviness), assurance (assurance), and empathy (emphasis) on member satisfaction is expected. The research method used a sample of 154 members, with questionnaire data collection and documentation and data analysis tools with multiple regression. The results showed : Y = 2,096 + 0,285X1 + 0,210X2 + 0,098X3 + 0,046X4 + 0,196X5 . This means that tangible variables, reliability, responsiveness, assurance and empathy have a positive effect on member satisfaction. The results of the F test show that the tangible, reliability, responsiveness, assurance and empathy variables have a simultaneous positive and significant effect on member satisfaction with the provisions of Fcount = 3.157 > Ftable = 2.31 then H0 is rejected and H1 is accepted. The results of the t-test, indicate that the tangible, reliability, responsiveness, assurance and empathy variables have a positive and partially significant effect on member satisfaction, this can be seen from the tcount of all variables > ttable 1.661 then H0 is rejected and H1 is accepted. The value of the correlation coefficient (r) = 0.745 means that the relationship between tangible variables, reliability, responsiveness, assurance and empathy for member satisfaction is very strong. The coefficient of determination (R Square) = 0.555 means that the tangible variables, reliability, responsiveness, assurance and empathy are able to explain the member satisfaction variable of 55.5% while 44.5% is explained by other factors. To increase the level of satisfaction of members, it is better to make various improvements related to the quality of services offered by KSP Mitra Usaha Mandiri, North Sumatra